Foreign language anxiety of Croatian EFL learners : : construction of an anxiety scale - Mihaljević Djigunović, Jelena (Array, 2004)
The paper focuses on the phenomenon of foreign language anxiety, and important affective learner factor that has recently become one of the most interesting topics in second language acquisition research. In the first part of the paper the authors give a brief theoretical overview of the concept and research findings to date. In the second they describe in detail the construction of an anxiety scale aimed at measuring language anxiety of Croatian L1 learners of English as a foreign language. The authors' underlying assumption and rationale for the study is that foreign language anxiety is culturally and socially determined and, thus, a valid instrument should be based on the cultural and social determinants of the population whose anxiety is to measure.